A study on the reliability and performance of solar powered street lighting systems - Fashina, Adebayo; Azeko, Salifu; Asare, Joseph; Ani, Chukwuemeka; Anye, Vitalis; Rwenyagila, Egidius; Dandogbessi, Bruno; Oladele, Omotoba; Dyeris, Murna (International Journal of Scientific World, 2017)
This paper presents the results of a study on the reliability and performance of the solar-powered street lighting systems installed at the African University of Science and Technology (AUST) in Nigeria, a hot and humid environment. The technical performance of the systems was studied using the following performance indicators: system energy yield, capture loss, as well as the system performance ratio while the reliability of the systems was examined using a model developed from the findings from the maintenance and fault diagnosis of the systems. The model was used to predict the total failure and survival probability of the systems using the Weibull distribution. The performance evaluation during the monitored period (February 2012 to January 2015) indicated that the performance ratios of the systems vary from 70% to 89% and the energy yields of the systems ranging from 2.87 h/day to 5.57 h/day. The results from the reliability analysis also showed that when the stress concentration factor around the notch between the cable terminals in the charge controller increases, the charge controller will become overheated, which in turn affected other components of the systems. The implications of this study are also discussed for the design and development of future solar-powered street lighting systems.